PENGARUH PENGGUNAAN MEDIA AUDIO VISUAL TERHADAP HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPAS PADA SISWA KELAS III SDN 8 MAMBORO (JS (JURNAL SEKOLAH), 2025)
Abstract: The purpose of this study was to determine the effect of the use of audiovisual media on student learning outcomes in science learning in grade III students of SDN 8 Mamboro. This type of research is a quantitative experimental research using the Quasi-experimental research method with a Nonequivalent Control Group Design research design. The subjects in this study were 38 students of grade III A and III B of SDN 8 Mamboro. The control class or class III A students numbered 20 people and the experimental class or class III B students numbered 18 people. Data collection was carried out using a research instrument in the form of a test. Data analysis used prerequisite tests, namely normality tests and homogeneity tests and hypothesis testing using independent sample t-tests assisted by the IBM SPSS statistical application program version 24. Based on the results of this study, a significant value of 0.008